Research on operating characteristics of single slide valve capacity control mechanism of the single screw refrigeration compressor. (December 2014) - Wang, Zengli; Liu, Zhan; Liu, Feilong; Yu, Xiaoling; Feng, Quanke
In the single screw refrigeration compressor (SSRC), the single slide valve capacity control mechanism (SVCCM) is the functional component used to achieve capacity control under different load conditions with cooperation of screw rotor and housing. In this paper, a new calculation model considering internal compression and leakage is presented to research the capacity control process and built-in volume ratio control process. By this model, the actual capacity and built-in volume ratio at different slide valve work locations can be determined using the calculated by-pass area and discharge area. The influences of structural parameters of the slide valve to the control characteristics of the capacity control process and the thermodynamic properties of the compressor are analyzed. Through the comparison of the capacity control process and the built-in volume ratio control process, the axial displacements of the slide valve required in the capacity control and in the built-in volume ratio control were obtained. All of this work can provide the basis for the later optimization design for the slide valve.